Efficacy and safety of decompressive craniectomy with non-suture duraplasty in patients with traumatic brain injury. - Tae Seok Jeong; Gi Taek Yee; Tae Gyu Lim; Woo Kyung Kim; Chan Jong Yoo (PLoS ONE, 2020)
Background Decompressive craniectomy is an important surgical treatment for patients with severe traumatic brain injury (TBI). Several reports have been published on the efficacy of non-watertight sutures in duraplasty performed in decompressive craniectomy. This study sought to determine the safety and feasibility of the non-suture dural closure technique in decompressive craniectomy. Methods A total of 106 patients were enrolled at a single trauma center between January 2017 and December 2018. We retrospectively collected data and classified the patients into non-suture and suture duraplasty craniectomy groups. We compared the characteristics of patients and their intra/postoperative findings such as operative time, blood loss, imaging findings, complications, and Glasgow Outcome Scale scores. Results There were 37 and 69 patients in the non-suture and suture duraplasty groups, respectively. There were no significant differences between the two groups concerning general characteristics. The operative time was significantly lower in the non-suture duraplasty group than in the suture duraplasty group (150 min vs. 205 min; p = 0.002). Furthermore, blood loss was significantly less severe in the non-suture duraplasty group than in the suture duraplasty group (1000 mL vs. 1500 mL; p = 0.028). There were no other significant differences. Conclusion Non-suture duraplasty involved shorter operative times and less severe blood losses than suture duraplasty. Other complications and prognoses were similar across groups. Therefore, the non-suture duraplasty in decompressive craniectomy is a safe and feasible surgical technique.